THE PSYCHOLOGY OF RELIGIOUS FUNDAMENTALISM - Puthenangady, Antony (Journal of Dharma, 2005)
The destruction, on December 6, 1992, of a mosque of the early Mughal period at Ayodhya, one of the most Hindu holy cities had sent shock waves not only across India and her neighbouring Muslim countries of Bangladesh and Pakistan, but even to the far away countries. It gave the impression to other countries that India abandoned or was about to abandon secularism, one of the most progressive features of the modern India. The tragedy at Ayodhya came as the climax of a long campaign on the part of a major political formation to incite religious sentiments to gain political ascendancy. The Country’s intellectual elite felt deep sorrow and asked the question where would the tendency to exploit religious sentiment and religious symbols for political ends lead India? The destruction of World Trade Centre on September 11, 2001 was another shock not only to United States of America but to the whole world. A perceived shock arose from a realization that no country is safe from the hands of fighting fundamentalists. Everybody was raising the concern over the consequences of recent wars in Afghanistan and Iraq. These events affect the internal harmony and the external security of every nation. What is behind all these is a mixture of religious bigotry and political opportunism.